Azolla microphylla Productivity Response to Inorganic Fertilizer (AB Mix) Application - Armi, Armi; Ridwan , Muhammad; Andalia, Nurlena; Yeni, Manovri; Sudana, Julia (Lembaga Teewan Journal Solutions, 2026)
Azolla microphylla is a type of fern plant that is small, lives in waters and is useful as a producer in the food chain and also water bioremediation. Azolla microphylla is a type of water fern plant that commonly grows in calm waters such as lakes, ponds, rivers, and rice fields. The purpose of this study is to determine the effectiveness of inorganic fertilizer application on the heavy growth of Azolla microphylla. The method used in this study was an experiment using a Complete Random Design (RAL) with 5 treatments and 4 repetitions. The results of the study showed that the application of inorganic fertilizers was effective against the heavy growth of Azolla microphylla. P3 treatment, namely the application of organic fertilizer with a dose of 70 ml to Azolla microphylla provides better growth than other treatments, because the nutrients in the inorganic fertilizer are balanced with the nutrient needs of the growth of Azolla microphylla. Application of AB mix fertilizer to the growth effectiveness of Azolla microphylla. The P3 treatment, namely the application of 70 ml of fertilizer to Azolla microphylla, provides better growth compared to other treatments. This shows that the application of inorganic fertilizer (AB mix) has a significant influence on the productivity of Azolla microphylla.